Book Review: Lumea cu Două Viteze. Puterile Emergente şi Țările Dezvoltate (Two-Speed World: Emerging Powers and Developed Countries) - Bogdan Mureşan (Romanian Journal of European Affairs)
This review analyses Paul Dobrescu’s Two-Speed World: Emerging Powers and Developed Countries, a brief volume made up of a collection of articles on various international relations and European affairs topics initially published by the Romanian professor in the “CLIPA” magazine in the 2010-2013 timeframe. Although sometimes lacking narrative consistency, the book emphasises the idea that the world in which we find ourselves is one with two speeds of development, characterised by a shifting centre of gravity from the West to the East, a tendency especially highlighted by the first decade of this century. By asking if the next century is going to be a Western one and if the European Union project, deeply hurt by the financial crisis, still has a future, Paul Dobrescu challenges his readers to think outside the box and paints a rather grim picture of things to come, with a society dominated by consumerism and a shortage in morality.